The EU and federalism polities and policies compared - Laursen, Finn (Ashgate Pub., 2011)
Tracing the evolution of federalist theory and the European Union (EU), this book features an international line up of experts who debate the pros and cons of treating the EU in a comparative context and ask whether a constitutional equilibrium has been reached in the EU.